Mass and cost figures for spatial axial three-phase electromagnetic systems with circular and hexagonal forming contours of twisted magnetic core rods - E.A. Avdieieva (National Technical University "Kharkiv Polytechnic Institute", 2014)
For a spatial three-phase axial electromagnetic system with double-contour phase elements of the twisted butt-end magnetic core, analytical dependences for optimal geometrical relations determination over minimum active part weight and cost criteria are obtained, advantages of the core elements hexagonal cross-section configuration shown.